IMPLIKASI PENAFSIRAN AL-QUR’AN TANPA ILMU NASIKH DAN MANSUKH - ., Muhsin . (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
This article wants to explain to readers the debate regarding Nasikh Mansukh's knowledge which is used as a basis or one of the methods of interpreting the Koran. The debate that emerged was that several interpretive figures did not believe in the existence of Nasikh Mansukh in the Koran. Even though the knowledge of Nasikh Mansukh is very important in interpreting the Koran, a small example that can be seen is determining the direction of the Qibla, you can imagine that we will face the Qibla anywhere. Then the issue of wills which are required when approaching death is removed by the inheritance verses and hadith of the Prophet Muhammad saw. By using the comparison method, the author will compare an interpretation that uses Nasikh Mansukh knowledge and one that does not use Nasakh Mansukh, as well as seeing what method is used if the interpretation does not use Nasakh Mansukh. The results of the research illustrate that interpreters who do not use nasikh mansukh use contextual and linguistic methods, apart from that there are also those who use am and takhsis in viewing the text without needing to eliminate the law.